Manipulation of Plastidial Protein Quality Control Components as a New Strategy to Improve Carotenoid Contents in Tomato Fruit - D’Andrea, Lucio; Rodriguez-Concepcion, Manuel (Frontiers in Plant Science, 2019)
Carotenoids such as β-carotene (pro-vitamin A) and lycopene accumulate at high levels during tomato (Solanum lycopersicum L.) fruit ripening, contributing to the characteristic color and nutritional quality of ripe tomatoes. Besides their role as pigments in chromoplast-harboring tissues such as ripe fruits, carotenoids are important for photosynthesis and photoprotection in the chloroplasts of photosynthetic tissues. Interestingly, recent work in Arabidopsis thaliana (L.) Heynh. has unveiled a critical role of chloroplast protein quality control components in the regulation of carotenoid biosynthesis. The accumulation (i.e. degradation rate) and activity (i.e. folding status) of phytoene synthase (PSY) and other Arabidopsis biosynthetic enzymes is modulated by chaperones such as Orange (OR) and Hsp70 in coordination with the stromal Clp protease complex. OR and Clp protease were recently shown to also influence PSY stability and carotenoid accumulation in tomato. Here we show how manipulating the levels of plastid-localized Hsp70 in transgenic tomato plants can also impact the accumulation of carotenoids in ripe fruit. The resulting carotenoid profile and chromoplast ultrastructure, however, are different from those obtained in tomatoes from transgenic lines with increased OR activity. These results suggest that different chaperone families target different processes related to carotenoid metabolism and accumulation during tomato ripening. We further discuss other possible targets for future manipulation in tomato based on the knowledge acquired in Arabidopsis.